Selection of a support matrix for the removal of some phenoxyacetic compounds in constructed wetlands systems - Dordio, Ana V. (2008)
The efficiency of constructed wetlands systems in the removal of pollutants can be significantly enhanced by using a support matrix with a greater capacity to retain contaminants by sorption phenomena, ionic exchange or other physico-chemical processes. The aim of this work was to evaluate the efficiencies of 3 different materials, Light Expanded Clay Aggregates [LECA] (in two different particle sizes), Expanded Perlite and Sand, for the removal from water of one pharmaceutical compound (clofibric acid) and one pesticide (MCPA). Both belong to the class of phenoxyacetic compounds. In addition, relationships were established between the compounds' removal efficiencies and the physico-chemical properties of each material. LECA exhibited a high sorption capacity for MCPA, while the capacity for clofibric acid was more modest, but still significant. In contrast, perlite had a very limited sorption capacity while sand did not exhibit any sorption capacity for any of the compounds. LECA with smaller particle sizes showed higher efficiencies than larger grade LECA and can achieve efficiencies near 100% for the lower concentrations in the order of 1 mg l− 1. However, the use of these smaller particle media at larger scales may present problems with hydraulic conductivities. The results show that expanded clay presents important advantages in laboratory studies and could be used as a filter medium or a support matrix in constructed wetlands systems.